2015
DOI: 10.1097/iae.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Retinopathy of Prematurity After Ranibizumab Treatment

Abstract: The role of anti-VEGF treatment for ROP is still being evaluated. Although the shorter half-life of ranibizumab makes it an attractive option, reactivation of ROP is possible. Physicians and families should be aware of this to follow infants closely for an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 19 publications
6
93
0
6
Order By: Relevance
“…Hu et al [24] presented 9 patients with reactivation of ROP after IVB injection. Wong et al [25] reported reactivations after IVR injection but not after IVB injection; they thought this might be due to the shorter half-life of ranibizumab. In our study, there was no significant difference between groups regarding the reactivation of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [24] presented 9 patients with reactivation of ROP after IVB injection. Wong et al [25] reported reactivations after IVR injection but not after IVB injection; they thought this might be due to the shorter half-life of ranibizumab. In our study, there was no significant difference between groups regarding the reactivation of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al [14] reported ROP reactivation in 5/6 eyes treated with IVR, whereas none of four eyes treated with IVB experienced reactivation. The reports by Wong and Erol seem to contradict the conclusion presented by Chen suggesting that IVB and IVR are equally effective, despite the fact that all three studies utilized the same dosage of anti-VEGF agents.…”
Section: Focus On Ranibizumab Versus Bevacizumabmentioning
confidence: 97%
“…Wong et al [25] found that reactivation after ranibizumab occurred between the 41st and 42nd weeks. In the present study, recurrence was observed in the postmenstrual 43rd week on average in the bevacizumab group and in the postmenstrual 42.2nd week on average in the ranibizumab group.…”
Section: Discussionmentioning
confidence: 99%